2013
DOI: 10.1017/s153759271200360x
|View full text |Cite
|
Sign up to set email alerts
|

Democracy and the Policy Preferences of Wealthy Americans

Abstract: It is important to know what wealthy Americans seek from politics and how (if at all) their policy preferences differ from those of other citizens. There can be little doubt that the wealthy exert more political influence than the less affluent do. If they tend to get their way in some areas of public policy, and if they have policy preferences that differ significantly from those of most Americans, the results could be troubling for democratic policy making. Recent evidence indicates that “affluent” Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 389 publications
(198 citation statements)
references
References 19 publications
8
180
1
9
Order By: Relevance
“…Using the 179 CCES respondents who reported at least $250,000 (roughly the top 4.5 percent of the income distribution), the corresponding correlations are .97 and .76. Some corroborating evidence comes from a comparison of the Survey of Economically Successful Americans (Page, Bartels, and Seawright 2013), based on a local sample of the wealthiest 1 percent or 2 percent of Americans, and the Inequality Survey (Page and Jacobs 2009), which was based on a representative sample of the American public. Eight policy-preference questions that were included on both surveys showed that the preferences of the top 25 percent of income earners generally fell about half way between those of the average citizen and those of the wealthy.…”
Section: American Democracy?mentioning
confidence: 98%
“…Using the 179 CCES respondents who reported at least $250,000 (roughly the top 4.5 percent of the income distribution), the corresponding correlations are .97 and .76. Some corroborating evidence comes from a comparison of the Survey of Economically Successful Americans (Page, Bartels, and Seawright 2013), based on a local sample of the wealthiest 1 percent or 2 percent of Americans, and the Inequality Survey (Page and Jacobs 2009), which was based on a representative sample of the American public. Eight policy-preference questions that were included on both surveys showed that the preferences of the top 25 percent of income earners generally fell about half way between those of the average citizen and those of the wealthy.…”
Section: American Democracy?mentioning
confidence: 98%
“…Vermögen in Umfragen oft unterrepräsentiert, was tendenziell zu einer Unterschätzung bestehender Einstellungsunterschiede führt. Um die Präferenzen der obersten Einkommensgruppen näher zu untersuchen, führen Page et al (2013) (Gilens 2015a, S. 226). Die Möglichkeit der direkten politischen Einflussnahme der "Superreichen" scheint deshalb vielen amerikanischen Autor_innen die naheliegendste Erklärung ungleicher Responsivität.…”
Section: Forschungsstandunclassified
“…In reality, politics and policy-making is heavily in uenced by special interest groups: Concerted e orts by relatively small but wealthy groups heavily shape policy in democratic systems, and the goals and preferences of special interest groups are usually di erent from the goals and preferences of the general population [15,16,17,18].…”
Section: Special Interest Groups In Politicsmentioning
confidence: 99%